2004
DOI: 10.1111/j.1537-2995.2004.00644.x
|View full text |Cite
|
Sign up to set email alerts
|

The cost‐effectiveness of screening blood donors for malaria by PCR

Abstract: The addition of PCR to the standard screening questionnaire is economically attractive compared to the current standard screening questionnaire.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 17 publications
1
24
0
Order By: Relevance
“…Since WNV assays have not yet been priced, we estimated their cost from studies of similar assays for other viruses. Other screening costs were obtained from state laboratories (R. Timperi, personal communication) and could be corroborated with data from a screening study [26] for transfusion-acquired malaria in Canada.…”
Section: Methodsmentioning
confidence: 82%
See 1 more Smart Citation
“…Since WNV assays have not yet been priced, we estimated their cost from studies of similar assays for other viruses. Other screening costs were obtained from state laboratories (R. Timperi, personal communication) and could be corroborated with data from a screening study [26] for transfusion-acquired malaria in Canada.…”
Section: Methodsmentioning
confidence: 82%
“…The cost estimates [2628] used in the base case are shown in Table 2. Direct costs for screening blood donors using WNV assays included screening kit and reagents, laboratory technician fees, and the costs of a discarded false positive, donor notification, and retrieval of a test-positive sample.…”
Section: Methodsmentioning
confidence: 99%
“…We believe, on the basis of our results, that detection of plasmodial DNA by the first step of nested-PCR, as has already been described in the detection of the Plasmodium genus 13 , would be enough to identify APCs with P. falciparum, P. vivax and P. malariae, thus reducing the costs of analysis in Brazilian blood banks. Furthermore, its cost-effectiveness was already approved in a Canadian study by a decision analysis model 18 . Additionally, the optimum strategy for minimizing the risk of transfusion-transmitted malaria in Brazilian endemic areas is a combination of appropriate donor selection together with donation screening using PCR and other laboratory methods.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to not using a medical questionnaire, the incremental cost-effectiveness ratio was $6,463 per case of malaria averted when using the medical questionnaire followed by PCR. 30 A third analysis was a costbenefit analysis with an implicit valuation of Israel's decision (in 1990s) to exclude blood donations from Ethiopian immigrants, due to the high prevalence of HIV infection in this community relative to the rest of the Israeli population. This analysis demonstrated that this exclusion policy could not be considered as justifiable on public health grounds if the annual social exclusion costs exceed $218,000 per year or $3.63 per Ethiopian immigrant.…”
Section: Health Technology Assessmentsmentioning
confidence: 99%